The effect of delegation and perceived organizational support on organizational identification and contextual performance - Lee, DongSun; Yoo, TaeYong (Korean Journal of Industrial and Organizational Psychology, 2011)
The first purpose of this study was to examine the influence of delegation and perceived organizational support(POS) on organizational identification and contextual performance. And the second purpose was to examine the moderating effect of growth need strength(GNS) on the relationship between delegation and organizational identification, and the moderating effect of dispositional cynicism on the relationship between POS and organizational identification. Data were gathered from 202 employees who were working in various organizations in Korea. To reduce the effect from common method bias, the contextual performance was rated by both self and others(twenty-two peers or supervisors). As results, the delegation and perceived organizational support had positive relationships with organizational identification. and organizational identification had mediating effect on the relationship between predictors(delegation and POS) and self-rating contextual performance. But there was no mediating effect of organizational identification on the relationship between predictors(delegation and POS) and other-rating contextual performance. The growth need strength had moderating effect on th relationship delegation and organizational identification because the relationship was more positive when GNS was high. Also dispositional cynicism had moderating effect on the relationship perceived organizational support and organizational identification because the relationship was more positive when dispositional cynicism was low. Finally, implication of results and future research tasks were discussed with limitations